The Full cupboard of life : more from the no.1 ladies detective agency - McCall Smith, Alexander, 1948- (Canada : Alfred A. Knopf, 2004)
Precious Ramotswe, owner of the No. 1 Ladies' Detective Agency in Botswana, wonders about the direction of her relationship with her boyfriend, while investigating the suitors of a wealthy entrepreneur in an attempt to determine whether they are after the woman's heart or her money.
Keywords: Mystery and detective stories